Self-healing geopolymer mortar - Mohd. Shukri, Muhamad Shardiq (2019)
Waste material from industrial product increase annually in Malaysia and become interesting topic on how to reduce recycling rate for sustainable eco-system. The application of geopolymer technology has become important around the world in preserves the environment from polluted. Furthermore, geopolymer contributed for less carbon dioxide emission and labelled as free cement content. The issue on defect are mainly concern after the construction because of several factor could cause structural or non-structural defect. In other hand, people perception about bacterial also be discussed in this research and give further explanation on their beneficial for ecosystems and construction industrial. This research presented an assessment on mechanical properties and self-healing in geopolymer fly ash mortar with addition effective microorganism in the design mixed. The development of new materials such effective microorganism that contribute like self-healing materials are needed to repair crack automatically and to restore or even increase mortar strength to prolong its service life. There are three type of specimens for different purposes in achieving research goal and testing of method or this research involving compressive strength test, self-healing test and permeability of geopolymer mortar The specimens have been cast and proper curing as follow as designed. Self-healing concept is discussed in detail result followed by the experimental program. . For conclusion, the aims to get ultimate strength from specimens and self-healing performance were successfully with experimental result. For further study are stated in recommendation.